Detrital zircon U–Pb–Hf isotopes study of the Lower Carboniferous Anjihai Formation from the northern margin of the Yili Block, NW China. (14th April 2018) - Wang, Meng; Zhang, Jinjiang; Pei, Xianzhi; Zhang, Bo; Chen, Youxin; Xiao, Zhibin; Zheng, Yanrong
Abstract : The North Tianshan Accretionary Complex represents a Late Palaeozoic suture between the Junggar Terrane and the Yili Block. We report detrital zircon U–Pb dating and Hf isotope results for a sandstone from the Lower Carboniferous Anjihai Formation in the northern margin of the Yili Block, to reveal the geochronological framework of the northern Yili Block, and discuss the subduction process of the North Tianshan Ocean (NTO). The detrital zircon ages were divided into 2 clusters, namely, the Precambrian and Palaeozoic ones. The Palaeozoic age group can be further divided into 3 subgroups, that is, 472–461 Ma, 448–423 Ma, and 406–335 Ma, with peaks at 465, 436, and 346 Ma, respectively. All the Palaeozoic zircons have oscillatory zoning textures and high Th/U ratios, showing an igneous provenance. The zircon Ti‐temperatures are between 584 and 809 °C, suggesting that their source rocks were I‐ or S‐type granitic rocks. In addition, most of the Palaeozoic zircons have positive εHf (t) values, indicating that the source rocks of the Palaeozoic zircons are derived from not only Mesoproterozoic continental crust but also involved depleted mantle components, which matched well with the Hf isotopic signatures of magmatic rocks from the northern Yili Block. Based on the regional geology, these zircons were thought to be sourced from magmatic rocks that were related to the subduction of the NTO. Taking into consideration the Middle–Late Ordovician arc‐type granitoids in the Wenquan area, we conclude that the northern margin of the Yili Block was a unified active continental margin in the Palaeozoic, and the subduction of the NTO started at least from the Middle Ordovician.